PENGARUH HARGA, LOKASI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA DIMSUM GAUL DI JAKARTA - Christine Aryani; Agus Wahyono (Jurnal Satya Mandiri Manajemen dan Bisnis, 2024)
This study aims to determine the effect of Price, Location and Quality of Service on Consumer Satisfaction at Dimsum Gaul in South Jakarta simultaneously or partially. The data used is primary data collected by distributing questionnaires to 100 respondents who have made purchases at Dimsum Gaul. Quantitative method and the results of this study are based on respondents' answers using a Likert scale. The analytical method used in this study is the Multiple Linear Regression Test, F Test, t Test and the Coefficient of Determination. The results of this study were processed with the help of SPSS 25 software indicating that by F Test (simultaneously) there is a significant influence between Price, Location and Quality of Service on Consumer Satisfaction. The t-test (partial) shows that price has no significant effect on consumer satisfaction, location has a significant effect on consumer satisfaction, and service quality has a significant effect on consumer decisions